Overall survival with immune checkpoint inhibitors across treatment settings and clinical and PD-L1-defined subgroups in advanced esophageal squamous cell carcinoma: a systematic review and meta-analysis of randomized trials - Bing Wang; Xiaoyu Han; Zengli Shen (Frontiers in Immunology, 2026)
Introduction To quantify overall-survival effects of immune-checkpoint-inhibitor (ICI)-containing regimens by treatment line and to evaluate whether clinical characteristics or PD-L1 definitions modify relative treatment benefit in advanced esophageal squamous cell carcinoma (ESCC). Methods PubMed, Embase, the Cochrane Central Register of Controlled Trials, and Web of Science were searched from inception through 1 August 2026. Two reviewers independently screened records, assessed full texts, extracted data, and evaluated risk of bias. Reports were linked to their parent randomized trial family. First-line single-checkpoint blockade plus chemotherapy and later-line checkpoint monotherapy were synthesized separately using REML random-effects models and modified Hartung-Knapp inference. Treatment-effect modification was quantified using within-trial ratios of hazard ratios (RHRs). Twenty-one interactions with at least two independent trial families entered Holm correction; Bonferroni correction was used as a sensitivity analysis. Results We identified 14 independent randomized trial families represented by 31 reports. The primary overall-survival analysis included 7 first-line trials ( N = 4,151; pooled HR 0.70, 95% CI 0.64–0.77; P < 0.001; I 2 = 0%) and 5 later-line trials ( N = 1,970; pooled HR 0.74, 95% CI 0.64–0.85; P = 0.004; I 2 = 0%). Of 30 post hoc line-specific interaction hypotheses, 28 had at least one eligible trial-family contrast: 21 met the k ≥ 2 pooling threshold and were included in multiplicity-adjusted analyses, 7 were single-trial descriptive contrasts, and 2 had no eligible estimate. None of the 21 pooled interactions remained significant after Holm correction; all Holm- and Bonferroni-adjusted P values were 1.000. The smallest unadjusted P value was 0.092 for first-line CPS ≥ 1 versus < 1. Discussion ICI-containing regimens improved overall survival in both first- and later-line settings, but aggregate within-trial interaction analyses did not identify a reliable clinical or PD-L1-defined treatment-effect modifier. Sparse subgroup reporting and the predominantly Asian evidence base limit the precision and generalizability of these findings. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/ , identifier CRD42024551725.